2019
DOI: 10.1007/s10198-019-01054-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life measured with the EQ-5D-5L: estimation of normative index values based on a representative German population sample and value set

Abstract: Background The generic and preference-based instrument EQ-5D is available in a five-response levels version (EQ-5D-5L). A value set for the EQ-5D-5L based on a representative sample of the German population has recently been developed. The aim of this study was to estimate normative values of the EQ-5D-5L index for Germany, and to examine associations between the EQ-5D-5L and selected sociodemographic factors. Methods The analysis was based on a representative sample (n = 4998) of the German general adult popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
103
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 28 publications
18
103
2
7
Order By: Relevance
“…In addition, the sample size of N = 309 was relatively small, thus results may not be generalizable to the older population at risk of falling in Germany. Furthermore, the selected sample reached better EQ-5D index values compared with normative values for the general German population of the respective age group [61]. This is most likely due to the exclusion of individuals who were cognitively impaired and had certain chronic conditions.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the sample size of N = 309 was relatively small, thus results may not be generalizable to the older population at risk of falling in Germany. Furthermore, the selected sample reached better EQ-5D index values compared with normative values for the general German population of the respective age group [61]. This is most likely due to the exclusion of individuals who were cognitively impaired and had certain chronic conditions.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…Even some health-related aspects may not be sufficiently captured in the five dimensions of the EQ-5D. Although the introduction of the 5-level version of the EQ-5D has improved the ability to differentiate between health conditions, ceiling effects remain a problem [61,62]. The results of this study should therefore be tested in future studies using different measures of (health-related) quality of life.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…To our knowledge, this is the first study to investigate the effects of HIIT on work ability, QoL and perceived stress in severely obese sedentary employees. Baseline assessments revealed that on average, participants had a moderate WAI (~ 35 points) with need for improvement [ 41 ], and EQ-VAS scores (~ 65%), that were lower compared to normative values in the general population [ 42 ]. Our results indicate that low-volume HIIT may positively affect work ability and well-being in severely obese individuals as became evident by significant improvements in WAI and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consists of a visual analogue scale (EQ-VAS, 0–100 points, higher values indicate higher QoL) and a descriptive system of 5 health-related QoL-dimensions (mobility, self-care, usual activities, pain/discomfort, anxiety/depression) with 5 severity levels each, which are converted to a single index value (EQ-5D-5L). An index value of 1.0 represents the best possible state of perceived health, while an index value of 0 represents the worst possible health status [ 42 ]. The Perceived Stress Questionnaire (PSQ) was applied to examine the perception of stress, including the 4 sub-factors “worries”, “tension”, “joy”, and “demands”.…”
Section: Methodsmentioning
confidence: 99%
“…The population norms produced in this study for patients with CLBP will be very helpful in feeding models aimed at predicting the impact of interventions on such patients. 33 34 Indeed, to our knowledge, no representative portrait of people living with CLBP has been conducted in Quebec, although some initiative exists with their geographical and inclusion criteria limits. 35 As a consequence, it is hard to say how close is our survey to a representative sample of this population.…”
Section: Discussionmentioning
confidence: 99%